PERBANDINGAN KEKUATAN SERTIFIKAT DENGAN PIPIL SEBAGAI ALAT BUKTI HAK MILIK ATAS TANAH GEGE DALAM PERKARA PERDATA NOMOR 2548/K/PDT/2017 (STUDI KASUS DI PENGADILAN NEGERI SELONG) - MASYHUR MASYHUR (Universitas Mahasaraswati K. Mataram, 2024)
This research aims to find out and analyze the comparison between the strength of certificates and pipel as evidence of rights to Gege land in civil case number 2548/K/Pdt/2017. In this research, the researcher formulated the problem of how the strength of the certificate compares with that of the certificate as evidence in civil case number 2548/K/Pdt/2017, and what the judge's consideration in case number 2548/K/Pdt/2017. This research is normative research which is adapted to the views expressed by experts. In this research, a statutory approach is used. The approach here is based on consideration of all relevant statutory regulations, then uses a conceptual and historical approach. The results of the research show a comparison of the strength of the certificate with the pipel as evidence of land rights over Gege in civil case number 2548/K/Pdt/2017. Based on the results of the research and discussion, it can be seen that the strength of the evidence of land ownership certificates as proof of ownership of land rights is conclusion that the land ownership certificate has valid legal force as long as the issuance of the certificate meets the requirements and procedures by applicable regulations, conversely if the issuance of the certificate does not meet the requirements and procedures then the certificate is administratively defective and is not legally valid.